Effect of Sonneratia caseolaris Fruit Flour Incorporation on the Physicochemical, Sensory and Nutritional Properties of Snack Bar - Mirza Gulam Ahmad; Puspitasari, Yunita Eka; Hardoko; Arisandi, Desy; Alimin, Raihan Muhammad; Sulistiyati, Titik Dwi (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2026)
This study aimed to evaluate the effect of (Sonneratia caseolaris) fruit flour incorporation on the physiochemical, sensory, and nutritional characteristics of snack bars. This study highlights the potential of mangrove-derived ingredients as functional components in value-added food products. The experiment employed a Completely Randomized Design (CRD) consisting of four substitution levels of pedada flour (0%, 5%, 10%, and 15%) with five replications. Snack bars were prepared by mixing dry and wet ingredients and baked at 120 °C for 20 minutes. Analyses included physical tests (hardness and color), sensory evaluation (taste, aroma, color, and texture), and chemical analyses (proximate composition, carbohydrate, tannin, HCN, and caloric content). The results demonstrated a statistically significantly effected (p<0.05) of pedada flour incorporation on all evaluated parameters. Hardness decreased with increasing pedada flour concentration, from 689.81 gF (0%) to 220.64 gF (15%). The best formulation was obtained at 5% pedada flour (TM2), with a hardness value of 495.34 ± 197.97 gF, a hue value of 73° (yellow-red), and the highest sensory scores for taste (3.34), aroma (3.28), and texture (3.06). Although the color score of TM2 was slightly lower than that of the control, it remained within the preferred color range. The proximate composition of the best formulation consisted of carbohydrates (55.97%), protein (9.71%), fat (9.08%), moisture (23.85%), ash (1.39%), and a caloric value of 344.44 kcal/100 g, with a yield of 65.1%. The 5% pedada flour addition produced the most balanced formulation in terms of physical quality, nutritional composition, and sensory acceptability.